1983
DOI: 10.1007/bf01234486
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic epoxide hydrolase in fetal and adult human liver

Abstract: The epoxide hydrolase and glutathione S-transferase activity towards styrene oxide as substrate were investigated and compared in fetal and adult human liver cytosols. The rate of formation of styrene glycol from styrene oxide (nmole/min/mg protein) was 0.23 +/- 0.02 (means +/- SE; n = 10) in fetal and 0.83 +/- 0.05 (means +/- SE; n = 14) in adult liver specimens. The enzyme followed Michealis-Menten kinetics in the fetal liver. In adult liver specimens the enzyme showed biphasic kinetics. For comparative purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Using styrene oxide as a substrate, EPHX2 exhibited activities of 230 pmol/min/mg protein in the fetal liver (10 specimens at 15 to 24 weeks gestation) with an approximate 4-fold increase in the adult (14 specimens, 29 to 69 years of age) (Pacifici et al, 1983a). A subsequent study with a more sensitive assay for trans-stilbene oxide hydration demonstrated EPHX2 as early as 14 weeks in the fetal liver (Pacifici et al, 1988).…”
Section: Epoxide Hydrolasementioning
confidence: 99%
“…Using styrene oxide as a substrate, EPHX2 exhibited activities of 230 pmol/min/mg protein in the fetal liver (10 specimens at 15 to 24 weeks gestation) with an approximate 4-fold increase in the adult (14 specimens, 29 to 69 years of age) (Pacifici et al, 1983a). A subsequent study with a more sensitive assay for trans-stilbene oxide hydration demonstrated EPHX2 as early as 14 weeks in the fetal liver (Pacifici et al, 1988).…”
Section: Epoxide Hydrolasementioning
confidence: 99%
“…Some phase II enzymes are already expressed at high levels since very early during gestation (e.g. epoxide hydrolase) (31). Interestingly, the glutathione‐ S ‐transferase (GST) activity is markedly reduced in spontaneous miscarriages at 28–36 weeks of gestation (32).…”
Section: Phase II Enzymesmentioning
confidence: 99%
“…Very little is known about these protective mechanisms in human fetal tissues. The epoxide hydrolase activity, which is involved in the detoxification of biologically active epoxides is found at a much lower level in fetal than in adult liver (17).…”
Section: Carcinogen Metabolism and Dna Repairmentioning
confidence: 99%